Design of a trial-based economic evaluation on the cost-effectiveness of employability interventions among work disabled employees or employees at risk of work disability: The CASE-study - Noben Cindy YG; Nijhuis Frans JN; de Rijk Angelique E; Evers Silvia MAA (BMC, 2012)
Abstract Background In the Netherlands, absenteeism and reduced productivity due to work disability lead to high yearly costs reaching almost 5% of the gross national product. To reduce the economic burden of sick leave and reduced productivity, different employability interventions for work-disabled employees or employees at risk of work disability have been developed. Within this study, called 'CASE-study' (Cost-effectiveness Analysis of Sustainable Employability), five different employability interventions directed at work disabled employees with divergent health complaints will be analysed on their effectiveness and cost-effectiveness. This paper describes a consistent and transparent methodological design to do so. Methods/design Per employability intervention 142 participants are needed whereof approximately 66 participants receiving the intervention will be compared with 66 participants receiving usual care. Based on the intervention-specific characteristics, a randomized control trial or a quasi-experiment with match-criteria will be conducted. Notwithstanding the study design, eligible participants will be employees aged 18 to 63, working at least 12 h per week, and at risk of work disability, or already work-disabled due to medical restrictions. The primary outcome will be the duration of sick leave. Secondary outcomes are health status and quality of life. Outcomes will be assessed at baseline and then 6, 12 and 18 months later. Economic costs will consist of healthcare costs and cost of lost production due to work disability, and will be evaluated from a societal perspective. Discussion The CASE-study is the first to conduct economic evaluations of multiple different employability interventions based on a similar methodological framework. The cost-effectiveness results for every employability intervention will be published in 2014, but the methods, strengths and weaknesses of the study protocol are discussed in this paper. To contribute to treatment options in occupational health practice and enable the development of guidelines on how to conduct economic evaluation better suited to this field; this paper provides an important first step. Trial registration Four trials involved in the CASE-study are registered with the Netherlands Trial Registry: Care for Work (NTR2886), Health and Motion (NTR3111), Guidance to Excel in Return to Work (NTR3151), Care for Companies/Second Care (NTR3136).